An Erotic Character of Knowing According to Kabbalah - Brylla, Dorota (Studia Warmińskie, 2014)
The article presents kabbalistic (i.e. from the medieval and later Jewish Mysticism) perspective on the idea of knowing, namely knowing that is defined and determined by the sexual union of man and woman. Since Kabbalah, when doing its interpretations, is based on the texts of Tanah, the starting point is made here the vers from the biblical Book of Genesis (4,1). The word jād‛a (ידע) (‘made love’/‘knew’) [Adam with Eve/Eve] from here is then lexically compared to the category of da‘at (דעת), „wisdom’, ‘knowing’, and the name of the kabbalistic sephira. Due to the role of this sephira in the doctrine of mystical judaism, the text presents the sexual connections that happen in the sephirotic dominium which form the pattern for the human relations. The ideal of these relations is on the material plane the attainment by man and woman (as an effect of the sexual zivvuga kadisha, an union between contradictory but complementary elements) the complete knowing (wisdom) of the partner, but also of God. This kind of spiritual knowing of God is determined by the fact that God is in Kabbalah the coincidentia oppositorum and the sephirotic structure.